Legal-Social Relations in Marriage Dispensation: A Comparative Study of the Tangerang Religious Court and the Serang Religious Court - Lutvia Prakasiwi; Muhammad Rizal Khoirul Umam; Izzul Mutho` (al-Afkar, Journal For Islamic Studies, 2026)
This study investigates the interplay between legal norms and social realities in marriage dispensation cases, through a comparative analysis of the Religious Courts in Tangerang City and Serang City. The increasing number of applications for underage marriage highlights the tension between statutory regulations and socio-cultural practices. Employing a socio-legal approach and qualitative methodology, the research draws on primary sources, including court decisions and interviews with judges, as well as secondary literature in the fields of law and social science. The findings demonstrate that, although both courts adhere to the same legal basic namely Law No. 16 of 2019 amending the Marriage Law there are marked differences in judicial reasoning shaped by local social contexts. The Tangerang court tends to prioritise procedural formality and child protection, whereas the Serang court shows greater accommodation of local cultural considerations. These variations underscore the extent to which legal decisions are influenced by the social environments in which they are embedded, reaffirming the dynamic relationship between law and society.